What really happened in the Garden of Eden? - Zevit, Ziony (New Haven : Yale University Press, 2013)
The Garden of Eden story, one of the most famous narratives in Western history, is typically read as an ancient account of original sin and humanity's fall from divine grace. In this highly innovative study, Ziony Zevit argues that this is not how ancient Israelites understood the early biblical text. Drawing on such diverse disciplines as biblical studies, geography, archaeology, mythology, anthropology, biology, poetics, law, linguistics, and literary theory, he clarifies the worldview of the ancient Israelite readers during the First Temple period and elucidates what the story likely meant in its original context. Most provocatively, he contends that our ideas about original sin are based upon misconceptions originating in the Second Temple period under the influence of Hellenism. He shows how, for Ancient Israelites, the story was really about how humans achieved ethical discernment. He argues further that Adam was not made from dust and that Eve was not made from Adam's rib. His study unsettles much of what has been taken for granted about the story for more than two millennia and has far-reaching implications for both literary and theological interpreters.
Introduction: The Fall is with us always -- Part 1. Now and then. The Fall in interpretation ; The Fall in the Hebrew Bible ; Who wrote the garden story and when? ; What is a reader-response approach to interpreting the garden story? ; Reading, presenting, and evaluating the garden story -- Part 2. Before then. A down-to-earth story (Gen 2:4-7) ; Why Eden? Why a garden? Where were the trees? (Gen 2:5, 8-10) ; Where in the world was Eden? (Gen 2:10-14) ; The gardener and his tasks (Gen 2:15) ; The second commandment (Gen 2:16-17) ; The first social welfare program (Gen 2:18-20) ; The first lady (Gen 2:21-23) ; Why "therefore"? (Gen 2:24) ; How bare is naked? (Gen 2:25) ; Clever conversation and conspicuous consumption (Gen 3:1-6) ; Dressing up for a dressing down (Gen 3:7-11) ; Interrogation and negotiation (Gen 3:11-13) ; Procreation in the garden (Gen 3:14-19; 4:1-2) ; Not a leg to stand on : the serpent's sentence and the Israelite culture of "curse" (Gen 3:14-15) ; No bundle of joy : Hawwa's sentence and Israelite predilections in legal reasoning (Gen 3:16) ; Toil and trouble : Adam's sentence and the rights of laborers (Gen 3:17-19) ; Out of the garden (Gen 3:20-24) -- Part 3. Then and now. The essential plot of the garden story ; A literal translation of a literary text ; Allusions to the garden story in the Hebrew Bible ; Contra the common interpretation ; Beyond the Tower of Babel -- Appendix: Transliterating Hebrew for tourists in the garden.
Includes bibliographical references (pages 335-355) and index.
Keywords: Eden; Fall of man; Bible -- Criticism, interpretation, etc